The Implementation of Adapted Physical Education at the End of the Pandemic: A Learning Evaluation - Erick Burhaein; Amalia Pratidina; Antika Pramesti Maharani Putri; Indah Hapsari Samudra; Luri Kusuma Wardani; Roihan Syafiq Pratama (Universitas Pendidikan Indonesia, 2024)
The prolonged pandemic period requires adaptive physical education teachers in Special Schools to do adjustments quickly to ensure that the learning process can run smoothly and learning objectives can be achieved. The purpose of this study was to analyze the implementation of adaptive physical education learning evaluation at the end of the pandemic. The research method used was the qualitative method with a phenomenological approach. The respondents were 20 active adaptive physical education teachers in Banjarnegara and Wonosobo regencies. Data collection instruments included documentation sheets, observations, and unstructured interviews. The results of this study showed that the education at the end of the Covid-19 pandemic was carried out online. The analysis of the findings is presented in 3 dimensions, namely 1) student engagement, 2) learning support, and 3) learning barriers. The evaluation used unstandardized observation rubric. It concludes that adaptive physical education learning in Special Schools during the pandemic was adjusted to the situation and conditions of the students. Cooperation between teachers and guardians is the key to a successful learning.